Plataforma destinada aos deficientes visuais para geração e digitalização de imagens - Silva, Rodrigo Luiz Araujo da (2015)
Currently multiple devices provide means of conveying information to the visually impaired through audio. However, if the interpretation of texts this resolved, there are few systems for interpretation and generation of graphics or symbols really functional. This paper presents a platform developed to generate and scan images on the computer and can be used by people with visual impairments. The device comprises hardware, a printed circuit board having an electrode array. Each electrode corresponds to a pixel, in analogy to the points on a display. In addition to the hardware, two programs were developed first, installed on computer analyzes and generates the image, the other is recorded in microcontroller and controls the electrode plate for pixel scan the pixel. When an object is positioned conductive based on the platform, the system checks which electrodes are with the closed contact and records these design points. This information is processed by dedicated software installed on your computer, which analyzes the information received, generates the design and the play on the computer screen. The device has been tested with applications of geometric shapes used in math classes and geometric shapes to build a flowchart. The device is a proposal for assistive technology tool that can help generate images of objects, flowcharts and diagrams in a simple and accessible way to people with low vision, facilitating the understanding and generate a wealth of detail in the information presented